Elephantine revisited: new insights into the Judean community and its neighbors - Folmer, Margaretha (Penn State University Press, 2022)
The Judean community at Elephantine has long fascinated historians of the Persian period. This book, with its stellar assemblage of important scholarly voices, provides substantive new insights and approaches that will advance the study of this well-known but not entirely understood community from fifth-century BCE Egypt. Since Bezalel Porten’s pioneering Archives from Elephantine, published in 1968, the discourse on the subject of the community of Elephantine during the Persian period has changed considerably, due to new data from excavations, the discovery and publication of previously unknown texts, and original scholarly insights and avenues of inquiry. Running the gamut from archaeological to linguistic investigations and encompassing legal, literary, religious, and other aspects of life in this Judean community, this volume stands at a crossroads of research that extends from Hebrew Bible studies to the history of early Jewish communities. It also features fourteen new Aramaic ostraca from Aswan. The volume will appeal to students and scholars of the Hebrew Bible and ancient Judaism, as well as to a wider audience of Egyptologists, Semitists, and specialists in ancient Near Eastern studies. In addition to the editor, the contributors to this volume include Annalisa Azzoni, Bob Becking, Alejandro F. Botta, Lester L. Grabbe, Ingo Kottsieper, Reinhard G. Kratz, André Lemaire, Hélène Nutkowicz, Beatrice von Pilgrim, Cornelius von Pilgrim, Bezalel Porten, Ada Yardeni, and Ran Zadok. Moreover, a video recording of an interview conducted with Porten on his long career in Elephantine studies accompanies the book through a link on the Eisenbrauns website